Evaluasi Program Pendidikan Antikorupsi yang Terintegrasi dalam Kurikulum Pendidikan Tinggi: Pendekatan CIPP dan Analisis SWOT: Evaluation of Anti-Corruption Education Program Integrated in Higher Education Curriculum: CIPP Approach and SWOT Analysis. - Asthadi Mahendra Bhandesa; I Wayan Lasmawan; I Gusti Putu Suharta; I Wayan Widiana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Anti-corruption education is a learning process and behavioral formation aimed at preventing corruption by developing anti-corruption behavior. The purpose of this study is to evaluate anti-corruption education integrated into the higher education curriculum at the Bali Institute of Technology and Health (ITEKES) through the CIPP approach and SWOT analysis. This research is a qualitative descriptive evaluative study that focuses on the policy analysis of the anti-corruption education program at the Bali Institute of Technology and Health. The research subjects included lecturers and students who had taken the anti-corruption education course. Data were collected through interviews and curriculum documentation studies.Furthermore, the data were evaluated using the CIPP (Context, Input, Process, Product) model and analyzed strategically using the SWOT method to identify strengths, weaknesses, opportunities, and threats related to the implementation of the policy. The CIPP approach analysis found that anti-corruption education was in accordance with Permenristekdikti No. 33 of 2019, with the support of expertise and facilities. Its implementation was through classroom learning processes and external activities, supported by socialization and leadership policies. There was an increase in anti-corruption knowledge, attitudes, and skills of the academic community. The SWOT analysis identified strengths such as the legal basis and leadership support, weaknesses in consistency and monitoring, opportunities from certified human resources and external networks, and threats from high levels of corruption and bureaucratic resistance, emphasizing the importance of commitment and consistency for the program's success. Anti-corruption education has been implemented in accordance with regulations, utilizing existing resources and infrastructure to improve anti-corruption knowledge, attitudes, and skills among the academic community through academic and non-academic activities. However, the program's success depends heavily on consistency, monitoring, and commitment from all parties, particularly in addressing corruption and internal resistance.